The Efficiency and Effectiveness of The Distribution of Zakat Funds in Yogyakarta 's Baznas - Muhammad Lutfi Hidayatulloh; Ade Nur Rohim; Sahlan Hasbi (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
Zakat is one of the instruments of economic development that is still minimal in maximizing its potential. Although the collection and distribution continues to increase every year, in fact there are still many problems in the zakat management organization. These problems include inefficiency in operational costs and HR costs in the Zakat Management Organization and the ineffective distribution of zakat to be able to convert mustahik into muzakki. This study aims to analyze the level of efficiency and effectiveness of the distribution of zakat funds in Yogyakarta’s Baznas. The research method uses a descriptive qualitative approach with secondary data from the publication of the Yogyakarta’s Baznas financial statements in 2017 – 2019 using an efficiency ratio with the Zakat Core Principle and Allocation to Collection Ratio. The results showed that the level of efficiency by using the total operating costs for the total amil rights, the total operational costs for the total collection and the total HR costs for the total collection for three years of operation was running efficiently. At the level of effectiveness using Gross ACR, Gross ACR Non-Amil, Zakah Allocation Ratio and Zakah Allocation Ratio Non-Amil has been effective for three years of operation. Recommendations from researchers are to always improve the collection and distribution of zakat funds so that they remain in the efficient and effective category.